Pengaruh Brand Awareness, Perceived Quality Dan Brand Image Terhadap Brand Satisfaction Dan Brand Loyalty Pada Jasa Biro Perjalanan Antar Kota Di Kota Malang - Pramono, Rendra Adi (Universitas Brawijaya, Indonesia, 2013)
The objective of this research is to analyse the effect of brand awareness, perceived quality, and brand image will make has brand satisfaction causing brand loyalty in each travel tour service consumer. The research population is entire customers that using services in three tour and travel companies in Malang city, that is Kirana Tour and Travel, Bali Prima Travel, and Siluet Travel. Variable from this research is brand awareness, perceived quality and brand image as independent variable, brand loyalty as variable dependen and brand satisfaction as variable intervening. The result of analysis shows several findings. First, when does level brand awareness that feeled travel tour customer increase, so brand satisfaction they will feel will increase also. This matter also be proved that level change brand awareness will influence customer loyalty level. Second, level perceived quality customer influences level brand satisfaction positively. Third, level change customer brand image at moment's notice will influence customer loyalty